Relational Mobility Increases Social (but Not Other) Risk Propensity - Li, L.; Hamamura, Takeshi; Adams, G. (2016)
In recent years, we have witnessed a resurgent focus on ecological features, especially various forms of mobility that afford social psychological processes. Extending this work, the current research examined whether relational mobility affects risk propensity. We conducted three studies using both correlational (Studies 1 and 3) and experimental (Study 2) methods. Results provide support for the hypothesis that perceptions of relational mobility are associated with risk propensity in the domain of interpersonal behaviors but not other risk domains (health, financial, etc.). Findings in Study 3 suggested that the association between relational mobility and propensity for risky interpersonal behaviors may stem from the effect of relational mobility in lowering subjective risk (but not in increasing expected benefits) of such behaviors. Copyright © 2015 John Wiley & Sons, Ltd.